TO SOME ORGANIZATIONAL ASPECTS OF ORGAN DONATION - M. Minina (Вестник трансплантологии и искусственных органов, 2010)
Organization of organ donation for transplantation is one of the most actual problems of Russian Transplantolo- gy. Organ shortage for transplantation is perceiving in Russia through the improvement of organizational system of organ donation. An analysis of efficiency of Russian Transplantology demonstrates that there are some parts in Russia showing very positive results in organ donation quite comparable to European data. But at the same time the potential of donor pool is realizing only partially for some reasons. Analysis of few of them is described in the paper.